Application of the Discovery Learning Model in Improving Motivation and Learning Outcomes Civic Education - Aulia, Cindy (International Journal of Students Education, 2024)
Student motivation in learning civics education tends to decrease. This is a challenge for teachers to improve student motivation and learning outcomes. Therefore, the application of an effective learning model is a solution for teachers to improve student motivation and learning outcomes in civics education learning. One model that can be implemented is the Discovery Learning learning model. The definition of the Discovery Learning learning model, according to (Prastowo 2018, p. 23) discovery learning is a series of activities or learning activities that can require students to be directly involved to the maximum, all the success of students to achieve and can analyze in an organized, critical, and logical way so that they can find their own knowledge, attitudes and skills so that there is a change in behavior. The main purpose of this study is to investigate the effectiveness and impact of the application of the Discovery Learning learning model in increasing student involvement and understanding in civics education learning. The method used in this study is the literature review study method. Through this study it can be concluded that Discovery Learning is able to increase student attraction in the learning process and students will also be assessed as more active and independent. However, the application of the Discovery Learning learning model may experience obstacles in the learning process, because the level of student understanding in critical thinking and student creativity abilities are certainly different. However, this can be minimized by having teachers as facilitators who can assess and evaluate the abilities and needs of students.